PENDIDIKAN KESEHATAN TERHADAP PENGETAHUAN DETEKSI DINI SELAMA KEHAMILAN DI DESA LEMAHDUWUR KECAMATAN KUWARASAN - Astuti, Dyah Puji; Kusumastuti, Kusumastuti (WARTA BHAKTI HUSADA MULIA : Jurnal Kesehatan, 2018)
Abstract: Early detection is important as the first attempt in the emergency management of pregnant women. Early detection activities are conducted in an effort to obtain information in the community as part of a preventive effort that can control the high maternal mortality rate in the community. Early detection is primarily done by the pregnant women themselves. The purpose of this study was to determine the characteristics and level of knowledge of pregnant women on early detection during pregnancy. This research method is descriptive analytic with cros sectional approach. The results showed that most respondents were in the category of healthy reproduction as much as 19 respondents (54.28%), 19 respondents (54.28%) in the multiparity category, 15 people (42.85%) in the advanced education category. There was a change in the level of knowledge of low respondents before given health education as much as 16 respondents (45, 71%) while after being given health education some respondents have a good level of knowledge that is as much as 16 respondents (45,72%). Â Â Keywords: health education, early detection, pregnant woment